PERLINDUNGAN HUKUM TERHADAP KREDITUR DALAM PEMBEBANAN HAK TANGGUNGAN OBJEK YANG BELUM TERDAFTAR - agustia, tria; Mirwati, Yulia; Azheri, Busyra (Universitas Muhammadiyah Sumatera Utara, 2020)
This research was conducted in the area of Tulang Bawang Regency, Lampung Province, where it was found that there were still very many people who only had a Land Certificate (SKT) or a Statement of Physical Ownership and Control of a Land Sector (Sporadic) as proof of land ownership and they wanted to get credit facilities by guaranteeing Land Certificate (SKT) or Statement of Ownership and Physical Control of the Land Sector (Sporadic). The subject matter examined is the legal protection in the imposition of mortgage rights of objects that have not been registered as collateral. This type of research is empirical research. The results showed that the legal protection of creditors in the imposition of mortgage rights for objects that have not been registered is holding on a credit agreement that is domiciled as the principal agreement that binds the parties that made it and on the power of attorney to sell the collateral that was signed when signing the credit agreement.This research was conducted in the area of Tulang Bawang Regency, Lampung Province, where it was found that there were still very many people who only had a Land Certificate (SKT) or a Statement of Physical Ownership and Control of a Land Sector (Sporadic) as proof of land ownership and they wanted to get credit facilities by guaranteeing Land Certificate (SKT) or Statement of Ownership and Physical Control of the Land Sector (Sporadic). The subject matter examined is the legal protection in the imposition of mortgage rights of objects that have not been registered as collateral. This type of research is empirical research. The results showed that the legal protection of creditors in the imposition of mortgage rights for objects that have not been registered is holding on a credit agreement that is domiciled as the principal agreement that binds the parties that made it and on the power of attorney to sell the collateral that was signed when signing the credit agreement.